Strengthening Blue Economy Through Sustainable Aquaculture Based on Islamic Economics and Local Wisdom - Istiqomah, Nur Hidayatul (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study employs a Systematic Literature Review (SLR) approach to examine the integration of Blue Economy, local wisdom, and Islamic economics as the foundation for sustainable marine development in Indonesia. The SLR method is conducted through a structured process of identifying, screening, and synthesizing relevant peer-reviewed journal articles, policy documents, and empirical studies from reputable academic databases such as Scopus, ScienceDirect, Web of Science, and Google Scholar using predefined keywords and inclusion criteria. The selected literature is analyzed using thematic synthesis to identify conceptual linkages between ecological sustainability, socio-cultural resilience, and Islamic ethical principles. This method enables the study to generate a comprehensive conceptual framework demonstrating that local wisdom serves as an adaptive ecological governance system, while Islamic values such as khalīfah, ‘adl, maṣlaḥah, and mīzān provide a normative foundation for justice and environmental stewardship. Furthermore, the review highlights the strategic role of Islamic financial instruments such as Blue Sukuk and productive waqf in funding sustainable marine projects, indicating that the synergy between Blue Economy, local wisdom, and Islamic economics can support a contextual and inclusive maritime development model for Indonesia.